Philanthropic advertising: Creative ways to raise awareness of humanitarian issues - (:unkn) unknown (Peter Lang Publishing Group, 2019)
Introduction Advertising can be a powerful engine for creating solutions and play a key role in solving humanitarian issues. Philanthropic advertising can deliver meaningful, permanent and creative solutions to raise collective awareness of humanitarian issues in contrast to traditional philanthropy, which raises only financial donations for a cause. In today’s world of isolated yet demanding television consumers, such creative ways are required to catch, maintain and direct people’s attention in a positive way. Philanthropic advertising helps to manage such demanding interests while continuing to also focus on the real, philanthropic issues. As a result, companies are seeking out more and finding more creative alternatives to motivate consumers to become involved with social issues, which, in turn, brings more attention to the effective use of advertising campaigns. The objectives of non-profit adverising and the profit-oriented ones are different. Philanthropy advertising tries to motivate donors to give time or money, where consumers are also quite different from each other. Profit-oriented ads aim to sell goods or services to consumers, while non-profit ads require consumers to consume their time and money for donation. Therefore, this type of charity positions itself as a firm to help people in need. This gives the donation on one’s own initiative. Thus, the individual obtains a moral satisfaction with the feeling that he is part of a good cause. Non-profit advertising is one of the most effective media tools for creating a perception. This perception is used to create an attitude towards…. © Peter Lang GmbH.